2005
DOI: 10.1590/s0004-282x2005000300032
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate and severe metabolic acidosis: case report

Abstract: -Topiramate infrequently induces anion gap metabolic acidosis through carbonic anhydrase inhibition on the distal tubule of the nephron -a type 2 renal tubular acidosis. We report on a 40 years old woman previously healthy that developed significant asymptomatic metabolic acidosis during topiramate therapy at a dosage of 100mg/day for three months. Stopping medication was followed by normalization of the acid-base status within five weeks. This infrequent side effect appears unpredictable and should be given c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Less commonly a variety of gastrointestinal symptoms have also been described [6]. Several reports describe toxicity at varying doses of ingestion when used for migraine and epilepsy (Table 2) [4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Based on a retrospective review of 567 cases of topiramate toxicity (during 2000-2001), the American Association of Poison Control revealed that: 39% were adults, mild mental status changes were common, and severe respiratory depression or persistent NAGMA were infrequent yet other reports confirm their occurrence [5,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly a variety of gastrointestinal symptoms have also been described [6]. Several reports describe toxicity at varying doses of ingestion when used for migraine and epilepsy (Table 2) [4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Based on a retrospective review of 567 cases of topiramate toxicity (during 2000-2001), the American Association of Poison Control revealed that: 39% were adults, mild mental status changes were common, and severe respiratory depression or persistent NAGMA were infrequent yet other reports confirm their occurrence [5,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The first three actions account for its intended neurological effects, whereas the fourth action induces a Type 2 renal tubule acidosis (RTA). The distal tubule of the nephron is unable to reclaim filtered bicarbonate, allowing increased urinary excretion, resulting in lowered serum bicarbonate levels (5,6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Burmeister et al [1] reported a case of a 46-year-old patient who was prescribed topiramate for vertigo and developed metabolic acidosis with a pH of 7.31 and serum bicarbonates of 8.9. Similarly, Ozer and Altunkaya [2] reported a case of a 58-year-old patient on topiramate for refractory temporal lobe epilepsy who developed metabolic acidosis with a pH of 7.29 and serum bicarbonates of 20 mM.…”
Section: Case Reportmentioning
confidence: 99%